2022
DOI: 10.31605/jstp.v3i1.1404
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan antara ukuran tubuh dan bobot badan pada induk sapi perah Friesian Holstein laktasi pertama

Abstract: This study aims to determine the relationship between body size and bodyweight of the first lactating FH dairy cow. The research method used was linear regression analysis with 17 individuals at 27-29 months. The observed variables were body weight (BW), body length (BL), shoulder height (SH), and chest circumference (CC). The results showed that the correlation value between BW and BL was 0.6791 with the correlation regression equation Y = -724.63+7.68X1. SH and BW have a correlation value of 0.4043. CC with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…Based on the results of the unpaired t test analysis, it can be concluded that there is no significant difference between the cows treated with steaming up and the cows without steaming treatment carried out by the Sumber Rejeki group on the weight of pregnant cows (t count < t table). Parent body weight is influenced by many factors such as genetics, nutritional content of the feed provided and management (Nurfitriani et al, 2021). Roche (2016) stated that the steaming treatment can increase the live weight of pregnant cows up to 0.7 kg and can increase milk production by 10-15% during the first 8 weeks of lactation.…”
Section: Effect Of Steaming Up On Body Weight Of Old Pregnant Parent ...mentioning
confidence: 99%
“…Based on the results of the unpaired t test analysis, it can be concluded that there is no significant difference between the cows treated with steaming up and the cows without steaming treatment carried out by the Sumber Rejeki group on the weight of pregnant cows (t count < t table). Parent body weight is influenced by many factors such as genetics, nutritional content of the feed provided and management (Nurfitriani et al, 2021). Roche (2016) stated that the steaming treatment can increase the live weight of pregnant cows up to 0.7 kg and can increase milk production by 10-15% during the first 8 weeks of lactation.…”
Section: Effect Of Steaming Up On Body Weight Of Old Pregnant Parent ...mentioning
confidence: 99%
“…Analisis korelasi merupakan suatu analisis yang digunakan untuk mengetahui sejauh mana hubungan dua variabel atau lebih. 11 Adapun rumus dari koefisien korelasi yaitu bentuk akar dari koefisien determinasi. Persamaan yang digunakan adalah: Tinggi badan memiliki rata-rata sebesar 1,69 meter dengan standar deviasi 0,05.…”
Section: Metodologiunclassified